Global World Markets in the First Half of 2020: Uncertainties, Trade Slowdown and Forced Protectionism under the Influence of National Isolation Measures - Anzorovich Shortanov, Rustam (2021)
Global world markets are often influenced by various macroeconomic factors that have both a positive and negative impact on their development. Recently, the whole world is experiencing, without exaggeration, a global economic catastrophe associated with the almost lightning-fast spread of a dangerous virus, the country of origin of which was China. The COVID-19 pandemic has caused unprecedented global upheavals that have had a major impact on societies in cities, countries, and regions. Most countries declared a nationwide lockdown in the first weeks of the pandemic, closing their borders to other countries. Moreover, at a time of global acute need for personal protective equipment, ALV and other medical devices and equipment, both air and sea transport were stopped, which separated the producing countries from the consumer countries. With soaring demand and the impact on supply chains, countries that had previously welcomed joint calls to fight the pandemic have entered a trade war in medical equipment. In the commodity market, the price of oil fell, leading to uncertainty about the future of oil-producing countries, as the end point of the pandemic was still unclear. Overall, the pandemic has been a severe test for the global economy. Due to the development of the pandemic, economists expect an unprecedented decline in industrial production and the percentage share of the stock exchange, rising commodity prices, as well as the possibility of reducing the GDP of a number of countries. While national Governments are trying to offset this drop in commodity prices, as well as for households, firms and financial markets, by providing economic assistance to affected groups, it is clear that such measures are not always viable. It is absolutely necessary to study the impact of COVID-19 on the global financial ecosystem in order to develop an effective trade policy. The danger of a pandemic is also exacerbated by the fact that a crisis in economic relations between countries can lead to political consequences that will cause an aggravation of the political situation in the world. The purpose of the work is to consider the development of world markets under the influence of various factors of uncertainty, the decline in production and trade under the influence of measures of national isolation.